New standards for eruption time and sequence of permanent dentition in Sri Lankan children. Issue 2 (3rd April 2019) - Jayatileke, Amali; Nawarathna, Lakshika S.; Ravishanker, Nalini; Wijekoon, P.; Nawarathna, Ruwan D.; Vithanaarachchi, V. S. N.; Wijeyaweera, R. L.
Abstract: This pioneering study aims to identify significant factors influencing the time to eruption of permanent dentition of Sri Lankan children and thereby establish standards for teeth eruption time and sequence. We analyzed a longitudinal data set consisting of 1, 073 students between 5 and 15 years of age from eight districts across Sri Lanka. The semi-parametric Cox proportional-hazards model was used to model time to eruption of each tooth as a function of several potentially useful covariates. A comparison of estimated hazard ratios established the general sequence of teeth eruption that is significantly different between jaws and across geographic locations, but not between genders. A new standard for permanent tooth eruption ages in Sri Lankan children is established.